Membrane Remodeling: Passive Crosslinkers Drive Membrane Tubulation - Braun, Marcus; Lansky, Zdenek (Current biology, 2020)
A new study has uncovered three mechanisms of motor-independent membrane tubulation. In vitro reconstitution using a minimal set of proteins shows that the accumulation of crosslinking proteins at the membrane-microtubule interface is sufficient to drive tubulation, which is enhanced by coupling with microtubule dynamics.
Keywords: proteiny; Proteins; mikrotubuly; Microtubules